PENERAPAN ALGORITMA C4.5 UNTUK PENERIMAAN KELAYAKAN KREDIT PADA KOPERASI (STUDI KASUS:KOPERASI XYZ) - Kelvin Kelvin; Bagus Mulyawan; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
In this developing era, competent human resources are still needed. Therefore, human resources is one of the factor in determining the successful implementation of organizations and companies. Despite having facilities and infrastructure as well as human resources with expected performance, the activities cannot be completed as they should. Based on this, a company, organization and cooperative must be able to manage existing human resources so that they can be obtained as needed.C4.5 algorithm is a group of decision tree algorithms that have input in the form of training samples and samples. Training samples are sample data that is used to build a tree that has been tested for correctness. While samples are data fields which will be used as parameters in classifying data. C4.5 algorithm aims to reduce and minimize errors in the provision of credit worthiness in cooperatives to the wider community.In this process we need an algorithm that is used to manage credit worthiness in cooperatives in order to facilitate the credit worthiness process. With this algorithm C4.5, it can be easier for admin to assess creditworthiness quickly and accurately.